Literature is a turtle that approaches the end of a trampoline (XXI Century. Spanish Literature and Culture, 2014)
In the following years the Humanities are going to confront some important challenges: some of them referred to the menaces of media industries, some of them linked to the stultification of the cultural and literary legacies. The young students who pretend to be researchers in Humanities will need in the future more and diverse theoretical tools to face this adversities, in order to stablish a true critic perspective about their work.
Keywords: criticism; Crisis of Humanities; Literary Theory; Saturated Cultures; Digital Theory